2017
DOI: 10.1080/01913123.2017.1362088
|View full text |Cite
|
Sign up to set email alerts
|

Value of transmission electron microscopy for primary ciliary dyskinesia diagnosis in the era of molecular medicine: Genetic defects with normal and non-diagnostic ciliary ultrastructure

Abstract: Primary Ciliary Dyskinesia (PCD) is a genetic disorder causing chronic oto-sino-pulmonary disease. No single diagnostic test will detect all PCD cases. Transmission electron microscopy (TEM) of respiratory cilia was previously considered the gold standard diagnostic test for PCD, but 30% of all PCD cases have either normal ciliary ultrastructure or subtle changes which are non-diagnostic. These cases are identified through alternate diagnostic tests, including nasal nitric oxide measurement, high speed videomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 59 publications
1
50
1
4
Order By: Relevance
“…, 2013 ; Wirschell et al. , 2013 ; Shapiro and Leigh, 2017 ). We predict that the PCD causing mutations in DRC1 and DRC2 likely disrupts the assembly of multiple axonemal substructures in human cilia similarly to that described here in Chlamydomonas .…”
Section: Discussionmentioning
confidence: 99%
“…, 2013 ; Wirschell et al. , 2013 ; Shapiro and Leigh, 2017 ). We predict that the PCD causing mutations in DRC1 and DRC2 likely disrupts the assembly of multiple axonemal substructures in human cilia similarly to that described here in Chlamydomonas .…”
Section: Discussionmentioning
confidence: 99%
“…Nasal nitric oxide gas is reduced in most patients with PCD [10]. Analysis of the respiratory epithelium by nasal brushing can be used for identification of ciliary structural defects by transmission electron microscopy (TEM) [113,118] and defects of the ciliary beat pattern and frequency can be identified by high-speed video microscopy analysis (HSVMA) [107]. HSVMA has excellent sensitivity and specificity for PCD and particular beat patterns have been linked to specific ultrastructural defects [15].…”
Section: Current Pcd Diagnosticsmentioning
confidence: 99%
“…For example, DNAH11 nonsense mutations are associated with subtle dynein arm modifications that can be detected only by advanced TEM imaging and tomography. 11 In this regard, approximately 30% of PCDaffected individuals showing ciliary dysfunction have no or very subtle ciliary ultrastructure abnormalities when investigated with standard transmission electron microscopy 58 Overall, our findings underline the evolutionary complexity of outer dynein arms assembly and trafficking. We have shown that bi-allelic mutations in LRRC56 are responsible for laterality defect in three unrelated families.…”
Section: Discussionmentioning
confidence: 61%